(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Thanks to the introduction of modern management strategies in the world, the scale of the effective use of vertical integration in innovative development of the industry is expanding. Therefore, the article deals with the introduction of modern innovative management strategies, the improvement of the organizational and economic mechanisms of processes ranging from the primary raw material to finished products, the effect of exogenous and endogenous factors affecting the production process, and the development of an effective organizational-economic mechanism of innovation activities of industrial enterprises about Developing scientific recommendations and practical recommendations aimed at improving the efficiency of the management of vertical integrated industrial enterprises based on innovation development.In the study, statistical analysis, experimental evaluation, economic mathematics, regression and correlation analysis, factor analysis methods.The relevance and accuracy of the approaches and methods used in the research is determined by the fact that the statistical data is based on the data of the State Statistics Committee of the Republic of Uzbekistan and other officially published data, and the relevant conclusions,